Regulation of Collagen Type I in Vascular Smooth Muscle Cells by Competition between Nkx2.5 and δEF1/ZEB1 - Ponticos, Markella (American Society for Microbiology, 2004)
A major component of the vessel wall of large arteries and veins is the extracellular matrix (ECM), which consists of collagens, elastin, and proteoglycans. Collagen type I is one of the most abundant of the ECM proteins. We have previously shown that the pro-collagen type I alpha 2 gene contains an enhancer which confers tissue-specific expression in the majority of collagen-producing cells, including blood vessels. In this paper, we delineate a specific vascular smooth muscle cell (vSMC) element: a 100-bp sequence around −16.6 kb upstream of the transcription start site that regulates collagen expression exclusively in vSMCs. Furthermore, we show that the expression is activated through the binding of the homeodomain protein Nkx2.5, which is further potentiated in the presence of GATA6. In contrast, this element was repressed by the binding of the zinc-finger protein δEF1/ZEB1. We propose a model of regulation where the activating transcription factor Nkx2.5 and the repressor δEF1/ZEB1 compete for an overlapping DNA binding site. This element is important in understanding the molecular mechanisms of vessel remodeling and is a potential target for intervention in vascular diseases where there is excessive deposition of collagen in the vessel wall.